O originário da arte em Martin Heidegger - Saiter, Cezario Caldeira (2017)
To search for an origin of artwork, for something that permeates all art, is a quest for the essence of art, but, as Martin Heidegger warns us in his lecture on the subject, essence is not something static and petrified, but what exists in itself. The path taken by the german philosopher starts from the most traditional ways in which art is thought, to arrive, from these same manners, to a new possibility of understanding where the true origin of art proceeds.